Getting the world back - about working in Hotel Pro Forma’s gravitational fi eld - Søndergaard, Morten; Orrù, Anna Maria; Søndergaard, Morten (Peripeti, 2017)
Morten Søndergaard about working in Hotel Pro Forma’s gravitational field